Effect of polypropylene fiber and shrinkage reducing admixture utilization on water absorption of Khorasan mortar - Kaya, Tugce Isafca; Karakuzu, Kemal; Ozen, Sueleyman; Dogangun, Adem; Aghabaglou, Ali Mardani (Elsevier, 2022)
It is seen that lime-based mortars are frequently preferred in historical and monumental structures. It is known that damages occur depending on the materials used in the building over time. In restoration works, mortars compatible with the original material of the building should be used. For this reason, the use of lime-based mortars is common during restoration work. Accordingly, attention should be paid to the physical and mechanical properties of the mortar to be produced. This study aims to determine the effect of polypropylene (PP) fiber and shrinkage reducing admixture (SRA) on the water absorption properties, which is used to improve the strength and durability properties of Khorasan mortar. As a result, it was determined that PP fiber utilization increased the water absorption ratio due to the formation of voids in the mortars. However, the use of SRA decreased the water absorption ratio due to its effect on the drying shrinkage behavior of the mortars. In cases where both are used together, the effect of fiber use was more dominant. Copyright (C) 2022 Elsevier Ltd. All rights reserved. Selection and peer-review under responsibility of the scientific committee of the Third International Conference on Aspects of Materials Science and Engineering.
3rd International Conference on Aspects of Materials Science and Engineering (ICAMSE) -- MAR 05-06, 2022 -- Chandigarh, INDIA
Keywords: Lime mortar; Khorasan mortar; Water absorption; Shrinkage reducing admixture; Polypropylene fiber